2018
DOI: 10.3390/ijms19102994
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Cytotoxic Analysis of Novel Hederagenin–Pyrazine Derivatives Based on Partial Least Squares Discriminant Analysis

Abstract: Hederagenin (He) is a novel triterpene template for the development of new antitumor compounds. In this study, 26 new He–pyrazine derivatives were synthetized in an attempt to develop potent antitumor agents; they were screened for in vitro cytotoxicity against tumor and non-tumor cell lines. The majority of these derivatives showed much stronger cytotoxic activity than He. Remarkably, the most potent was compound 9 (half maximal inhibitory concentration (IC50) was 3.45 ± 0.59 μM), which exhibited similar anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…The IC 50 of derivatives compound 7e were 2.05 ± 0.66 µM, 2.79 ± 0.53 µM, 3.52 ± 0.37 µM and 3.13 ± 0.84 µM against Hela, HepG-2, BGC-823 and SK-SY5Y, respectively. It was further verified that the small molecule nitrogen heterocycle could enhance BA's bioactivity, which was in line with our previous report [20].…”
Section: Cytotoxicitysupporting
confidence: 91%
“…The IC 50 of derivatives compound 7e were 2.05 ± 0.66 µM, 2.79 ± 0.53 µM, 3.52 ± 0.37 µM and 3.13 ± 0.84 µM against Hela, HepG-2, BGC-823 and SK-SY5Y, respectively. It was further verified that the small molecule nitrogen heterocycle could enhance BA's bioactivity, which was in line with our previous report [20].…”
Section: Cytotoxicitysupporting
confidence: 91%
“…The antitumor activity was assessed by MTT assay, as previously reported ( Fang et al, 2018 ). Each tested compound and positive control drugs were dissolved in DMSO and diluted with the medium to the test concentrations, and the final concentration of DMSO in the culture medium was controlled at less than 0.5% (v/v).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore (3R,4S)-3-(4-bromophenyl)-4-(4-fluorobenzoyl)-2-(2-oxo-2-phenylethyl)-3,4-dihydropyrrolo [1,2-a] pyrazin-2-ium bromide, synthesized based on pyrrolo [1,2-a] pyrazine, was suggested as a novel potential anticancer agent via caspase-3 activation and PARP cleavage ( Seo et al, 2020 ). Previously, we had reported the preparation of a series of novel natural product derivatives with ligustrazine (2,3,5,6-tetramethylpyrazine, TMP) which was a major effective component of Ligusticum chuanxiong Hort and observed that these derivatives possessed potent selective cytotoxicity ( Xu et al, 2015 ; Bi et al, 2016 ; Xu et al, 2017 ; Wang H. et al, 2018 ; Wang P. et al, 2018 ; Fang et al, 2018 ). Meanwhile, we synthesized hederagenin derivatives containing pyrazines with different methyl numbers and positions, and most of these derivatives showed much stronger cytotoxicity than the parent compound ( Fang et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, amino acids successfully gained our attention because of its neuroprotection. For instance, L-type lysine could improve the function of central nervous tissue [32], glycine can reduce the damage of toxic substances generated during the ischemic processes and generate neuroprotective effects [33] and the neuroprotective effect of sarcosine is associated with changes in glycine transport and reduction of NR2B-containing NMDAR expression [34,35]. Therefore, they have inspired our interest in using diosgenin as the template parent to synthesize novel neuroprotective agents by combination with amino acids.…”
Section: Introductionmentioning
confidence: 99%